Somatic embryogenesis response in Argentinian sugarcane genotypes for in vitro mutagenesis application - Di Pauli, Valentina; Fontana, Paola Daniela; Lewi, Dalia Marcela; Felipe, Arturo; Erazzu, Luis Ernesto (International Society of Sugar Cane Technologists, 2022)
XXX Congress of the ISSCT (International Society of Sugar Cane Technologists), Tucumán, from 31 August to 8 September 2019